Population Pharmacokinetic Analysis of Tiropramide in Healthy Korean Subjects - Seung-Hyun Jeong; Ji-Hun Jang; Hea-Young Cho; Yong-Bok Lee (MDPI AG, 2020)
The purpose of this study was to perform population pharmacokinetic (PPK) analysis of tiropramide in healthy Korean subjects, as well as to investigate the possible effects of various covariates on pharmacokinetic (PK) parameters of tiropramide. Although tiropramide is commonly used in digestive system-related diseases as an antispasmodic, PPK reporting and factors affecting PKs are not clearly reported. Thus, this study for healthy subjects is very significant because it could find new covariates in patients that had not been reported before or predict PPK for patients in the clinic by establishing PPK in healthy adults. By using Phoenix NLME, PK, demographic, and genetic data (collected to explain PK diversity of tiropramide in population) analyses were performed. As a basic model, a one-compartment with first-order absorption and lag-time was established and extended to include covariates that influenced the inter-subject variability. The total protein significantly influenced the distribution volume and systemic clearance of tiropramide, but genetic factors such as ABCB1 (1236C>T, 2677G>T/A, and 3435C>T), CYP2D6 (*1 and *10), OCT2 (808G>T), and PEPT1 (1287G>C) genes did not show any significant association with PK parameters of tiropramide. The final PPK model of tiropramide was validated, and suggested that some of the PK diversity in the population could be explained. Herein, we first describe the establishment of the PPK model of tiropramide for healthy Korean subjects, which may be useful as a dosing algorithm for the diseased population.